The Technogenic civilization: conceptual foundations and dynamics trends - Novikov, Vladimir T.; Novikova, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The nature of technogenic society and specific features of its dynamics are considered. The theoretical basys of the issue is related to the technogenic society conception masterminded by V. S. Stepin. The methodological significance of such notions as «man», «human», «nature», «activity», «traditions and innovations», «personality», «rationality», «power» is revealed whereas the analysys of these concepts allows us to characterize the conditions of genesis and evolution of technogenic society. The attention is paid on actual problems of its dynamics as far as the focus is made on the role of the creative technologies. The threats and risks in appliance of these technologies are accentuated.